The Impacts of Organizational Changes on Negative Emotion Resulting on Employee Resistance in the Insurance Office of PT Asuransi Cakrawala Proteksi Indonesia (ACPI) - Parwati, Azuarini Diah; Patiro, Shine Pintor S; Minrohayati (Ilomata International Journal of Management, 2024)
Recently, the insurance industry has been dealing with industrial revolution 4.0, which is a major change in the technology sector that causes many changes in other sectors. The industrial revolution 4.0 begins with the utilization of moveable and controllable machines in the production process. It starts from using simple robots to sophisticated computers. The potential impact of Industry 4.0 is the emergence of employee resistance to change in the organization. This research aims to reveal, analyze, and discuss the role of organizational changes in predicting negative emotions and impacts on resistance to change. The sample used in this research was 101 participants, who were employees at PT Asuransi Cakrawala Prokteksi Indonesia (ACPI). Then, the sampling technique used saturated sampling and a questionnaire as a data collection tool. Structural Equation Modeling (SEM) analysis was used as a data analysis technique using the SMART PLS 3 application. The results of this research indicate that organizational change caused significant negative emotions among employees. Eventually, employees became resistant. The limitation of this research was that it only involved employees of the ACPI’s insurance office in all regions of Indonesia, so the generalization of the results of the research could not be conducted.